Metallic nanoparticles affect uptake of polycyclic aromatic hydrocarbons and impacts in the Mediterranean mussels Mytilus galloprovincialis. (March 2023) - Bouzidi, Imen; Sellami, Badreddine; Boulanger, Anna; Joyeux, Cecile; Harrath, Abdel Halim; Albeshr, Mohammed Fahad; Pacioglu, Octavian; Boufahja, Fehmi; Beyrem, Hamouda; Mougin, Karine
Abstract: The impact of metallic nanoparticles (NPs) on the uptake and toxicity of persistent organic pollutants by marine bivalves was assessed through a comparative laboratory study by exposing mussels to polycyclic aromatic hydrocarbon (PAHs), in the presence and absence of ZnO and TiO2 NPs. PAHs and NPs concentration was analyzed after 14 days of exposure in mussels by GC/MS and ICP/AES. Furthermore, impact on the physiology and neurotoxicity of PAHs and NPs acting alone or in mixtures were also determined. Our results confirmed the bio-uptake of PAHs and NPs by mussels. In addition, the exposure NPs-PAHs resulted in different bio-uptake profile to that of PAHs alone. The NPs and accumulation of PAHs led to disturbance of essential metals concentration and to different impact profiles in the filtration and respiration capacities as well as in the acetylcholinesterase activity. Antagonist interactions between NPs and PAHs could occur after exposure. Highlights: Mussels accumulated Ti and Zn when exposed to TiO2 NPs and ZnO nanoparticles (NPs). PAHs accumulation and toxicity in mussels depend to the presence of NPs. Decrease of some PAHs concentrations in the presence of NPs suggests their interactions.